2007
DOI: 10.1038/sj.onc.1210640
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the fusion of TMPRSS2 to ERG sequences identifies fatal human prostate cancer

Abstract: New predictive markers for managing prostate cancer are urgently required because of the highly variable natural history of this disease. At the time of diagnosis, Gleason score provides the gold standard for assessing the aggressiveness of prostate cancer. However, the recent discovery of TMPRSS2 fusions to the ERG gene in prostate cancer raises the possibility of using alterations at the ERG locus as additional mechanism-based prognostic indicators. Fluorescence in situ hybridization (FISH) assays were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
378
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(416 citation statements)
references
References 35 publications
29
378
4
2
Order By: Relevance
“…From a case -control study by Lapointe et al (2007), where 54 patients with localised cancer and 9 patients with metastasis were examined for fusion status, no correlations were found with stage, grade or recurrence. On the other hand, large cohort studies of patients managed with watchful waiting did show correlations with a positive fusion status being associated with reduced survival (Attard et al, 2007;Demichelis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a case -control study by Lapointe et al (2007), where 54 patients with localised cancer and 9 patients with metastasis were examined for fusion status, no correlations were found with stage, grade or recurrence. On the other hand, large cohort studies of patients managed with watchful waiting did show correlations with a positive fusion status being associated with reduced survival (Attard et al, 2007;Demichelis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared clinicopathological parameters (Perner et al, 2006;Wang et al, 2006;Lapointe et al, 2007;Rajput et al, 2007;Tu et al, 2007) and prognostic significance (Wang et al, 2006;Attard et al, 2007;Demichelis et al, 2007;Lapointe et al, 2007;Nam et al, 2007) of this gene fusion with conflicting results. Two of these studies showed no correlation between histologic grade (Gleason score) (Lapointe et al, 2007;Tu et al, 2007), while others found positive associations (Attard et al, 2007;Rajput et al, 2007). Also, some studies have only shown correlation of fusion status with tumour stage (Perner et al, 2006;Wang et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Advantageously to routine detection of ERG fusion, FISH can give qualitative information on the type of gene fusion, resulting either from translocation or deletion, which is reported to be of clinical relevance. [5][6][7] Application of FISH, however, needs tissue-dependent optimization and can suffer from difficulty in interpretation, especially when only a few atypical glands are present. On the other hand, both quantitative and qualitative information on gene fusion can be obtained by QPCR.…”
mentioning
confidence: 99%
“…Another RNA-based marker, TMPRESS2-ERG fusion gene, which is expressed in over half of the cases of clinically localized prostate cancer [74], has also shown recent promise as an prognostic factor. Several studies show associations with histological grade [75,76] and tumor stage [77,78]. Investigators reviewed tissue samples of 226 men who were treated with radical prostatectomy and found that in those for positive TMPRSS2-ERG fusion gene expression (N = 114, 50.4 %), PSA, Gleason sum, and margin status were independently associated with biochemical and progression-free survival [79].…”
Section: Future Directionsmentioning
confidence: 99%